MICROMORPHOMETRIC CHANGES IN RATS’ SPLEEN IN THE FIRST 7 DAYS AFTER SKIN BURNS AND UNDER APPLICATION HYPEROSMOLAR COLLOID SOLUTIONS - Ocheretna, N.P. (World of Medicine and Biology, 2015)
In this work on the laboratory white male rats weighing 155-160 g studied stereometric relative volume changes of white and red pulp of the spleen under the influence of drugs infusion 0.9% solution of NaCl, lactoproteins with sorbitol and HAES-LX-5% after 1, 3 and 7 days without burns and after burns skin damage II-III degree with affected area 21-23% of body surface. Found no change of data stereometric parameters when injected to animals without skin burns during the first seven days these solutions. When using hyperosmolar colloid infusion solutions lactoproteinum with sorbitol and HAES-LX-5% from the third day after burn of skin there is a pronounced positive correction changes of relative volume of white and red pulp of the spleen, compared with the use of 0.9% solution of NaCl.
Keywords: spleen; rats; stereometry; skin burns; colloidal hyperosmolar solutions